2023
DOI: 10.2147/jaa.s410592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biologic Therapies on Airway Hyperresponsiveness and Allergic Response: A Systematic Literature Review

Abstract: Background: Airway hyperresponsiveness (AHR) is a key feature of asthma. Biologic therapies used to treat asthma target specific components of the inflammatory pathway, and their effects on AHR can provide valuable information about the underlying disease pathophysiology. This review summarizes the available evidence regarding the effects of biologics on allergen-specific and nonallergen-specific airway responses in patients with asthma. Methods: We conducted a systematic review in accordance with Preferred Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Finally, tezepelumab (anti-TSLP) has broad suppressive effects on type 2 inflammatory pathways, reducing the activity of IL-4, IL-5 and IL-13, as evidenced by reductions in blood and airway eosinophil counts, and FeNO and serum total IgE levels [ 10 , 11 ]. Tezepelumab has also been shown to reduce airway hyperresponsiveness [ 12 , 13 ], likely through type 2-dependent and -independent effects on airway smooth muscle and mast cell activation [ 39 41 ]. In addition to varying mechanisms of action of the biologics discussed, differences in study design, study populations and inclusion/exclusion criteria between trials could also contribute to the observed differences in AAER reductions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, tezepelumab (anti-TSLP) has broad suppressive effects on type 2 inflammatory pathways, reducing the activity of IL-4, IL-5 and IL-13, as evidenced by reductions in blood and airway eosinophil counts, and FeNO and serum total IgE levels [ 10 , 11 ]. Tezepelumab has also been shown to reduce airway hyperresponsiveness [ 12 , 13 ], likely through type 2-dependent and -independent effects on airway smooth muscle and mast cell activation [ 39 41 ]. In addition to varying mechanisms of action of the biologics discussed, differences in study design, study populations and inclusion/exclusion criteria between trials could also contribute to the observed differences in AAER reductions.…”
Section: Discussionmentioning
confidence: 99%
“…The only other drug, which is currently not marketed for asthma, that achieved the result of reducing AHR was etanercept in one study. In the end, the only two drugs that are currently available for asthma and able to reduce AHR are tezepelumab and omalizumab [ 93 ].…”
Section: T2 Targeted Therapies In Asthmamentioning
confidence: 99%